Intracellular aggregation of peptide-reprogrammed small molecule nanoassemblies enhances cancer chemotherapy and combinatorial immunotherapy - Jinrong Peng; Yao Xiao; Qian Yang; Qingya Liu; Yu Chen; Kun Shi; Ying Hao; Ruxia Han; Zhiyong Qian (Elsevier, 2021)
The intracellular retention of nanotherapeutics is essential for their therapeutic activity. The immobilization of nanotherapeutics inside target cell types can regulate various cell behaviors. However, strategies for the intracellular immobilization of nanoparticles are limited. Herein, a cisplatin prodrug was synthesized and utilized as a glutathione (GSH)-activated linker to induce aggregation of the cisplatin prodrug/IR820/docetaxel nanoassembly. The nanoassembly has been reprogrammed with peptide-containing moieties for tumor-targeting and PD-1/PD-L1 blockade. The aggregation of the nanoassemblies is dependent on GSH concentration. Evaluations in vitro and in vivo revealed that GSH-induced intracellular aggregation of the nanoassemblies enhances therapeutic activity in primary tumors by enhancing the accumulation and prolonging the retention of the chemotherapeutics in the tumor site and inducing reactive oxygen species (ROS) generation and immunogenic cell death. Moreover, the nanoassemblies reinvigorate the immunocytes, especially the systemic immunocytes, and thereby alleviate pulmonary metastasis, even though the population of immunocytes in the primary tumor site is suppressed due to the enhanced accumulation of chemotherapeutics. This strategy provides a promising option for the intracellular immobilization of nanoparticles in vitro and in vivo.